Penggunaan model problem based learning untuk meningkatkan kemampuan berpikir kritis peserta didik kelas IV Sekolah Dasar - Suci Nursyamsiah; Hana Sakura Putu Arga; Evi Susanti (COLLASE (Creative of Learning Students Elementary Education), 2026)
The background underlying the research is the low critical thinking abilities of students, especially in science and science learning. This research aims to determine the improvement in critical thinking skills of fourth grade elementary school students using the problem based learning model, the obstacles of teachers and students in learning using the problem based learning model. The research method used is a mix method with a sequential explanatory design. A total of 36 class IV students at one of the Bandung Regency elementary schools were used as research subjects, consisting of 19 boys and 16 girls. The data collection process was obtained from test questions, observation sheets and teacher interviews, as well as student response questionnaires. The results of the research show that by implementing the problem based learning model, an n-gain analysis of 76% was achieved in the effective category, and had an effect on students' average score from the pretest and posttest process, which was initially 52.33 to 88.33. This shows that the problem based learning model is effective in improving students' critical thinking abilities. The obstacles faced by teachers are at the grouping stage, time conditioning, and students' mastery of the material. Meanwhile, the obstacles experienced by students are difficulties in strengthening their opinions, considering information and assessing the results of discussions. Keywords: Critical Thinking Ability, Problem Based Learning Model, Science Learning